Consumers’ interest in using clothing repair services in Finland - Karell, Essi; Niinimäki, Kirsi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Sustainable consumption practices, including garment repair, are vital in transition to a circular economy. Engaging in garment repair through professional repair services is, however, not as widely adopted practice as one might hope. This paper focuses on clothing repairs in the Finnish context, aiming to understand how consumers perceive the use of clothing repair services and what might be the reasons for not using these services. An online survey was conducted in 2021 to address this topic as part of a collaboration between the FINIX research project and the Finnish retail and service network S Group. Based on 1,903 survey responses, consumers generally express interest in the sustainable aspects of clothing and recognize themselves playing an important role in extending garment lifetimes. The use of clothing repair services remains yet relatively moderate among Finnish consumers. Many are competent in repairing garments themselves and do not require professional help. Price and availability are other critical factors that discourage consumers from using such services. Establishing a viable repair business may be challenging, given the price levels consumers are willing to pay for garment repairs.